A Technology for Forming Tablet Cores of Complex Geometric Shapes for Further Coating, with a Multivitamin Product as a Case Study - V. V. Kosenko; A. V. Bolotova; A. S. Gavrilov; N. D. Bunyatyan; V. A. Evteev; A. M. Shevchenko; A. B. Prokofiev (Регуляторные исследования и экспертиза лекарственных средств, 2025)
INRODUCTION. The traditional technology of layering components onto sugar granules to produce medicinal products in the form of dragees has a number of disadvantages, including labour intensity, as well as the exposure of intermediates to liquids and high temperatures at certain production stages, which reduces the stability and effectiveness of the resulting medicinal products.AIM. This study aimed to develop an alternative technology for producing coated spherical tablet cores, with a multivitamin product as a case study.MATERIALS AND METHODS. The active ingredients used were retinol acetate, ascorbic acid, thiamine hydrochloride, and riboflavin. The excipients used included fillers (glucose, sorbitol, isomalt, and microcrystalline cellulose), glidants (talc and magnesium stearate), coating components (hydroxypropyl methylcellulose and titanium dioxide), etc. Tablet masses were produced by mixing accurately weighed amounts of active substances and excipients in a mixer for powdered materials. Individual tablet cores and tablets were weighed using a Shimadzu UW220H laboratory balance. They were tested for resistance to crushing using an Erweka TBH 125 tablet hardness tester. The content of water-soluble vitamins was determined by high-performance liquid chromatography (HPLC) in accordance with analytical procedures developed for Revit dragees by Uralbiofarm JSC. The labour intensity of multivitamin manufacturing technologies was estimated as the time required to produce a package of 100 dragees (by production process stage), and their efficiency was evaluated based on the process yield.RESULTS. As an alternative to the traditional technology for producing dragees, the authors developed a new direct compression and coating technology involving the use of 7.0 mm concave punches with a 4 mm curvature radius to obtain spherical tablet cores for coating. Pilot-scale industrial tests confirmed smooth equipment operation and compliance of tablet cores/finished medicinal products with the applicable regulatory requirements. This study demonstrated the possibility of producing spherical tablet cores with a mass of 0.27±0.01 g, friability of 0.6±0.1%, disintegration time of 4.3±1.2 min, and resistance to crushing of 48.2±7.4 N. Subsequent coating of tablet cores resulted in finished medicinal products indistinguishable in appearance from traditional dragees. The yield of finished medicinal products was 87.14% for sugar-coated tablet cores and 91.07% for suspension-coated tablet cores. The study showed the traditional technology for producing dragees to be 1.8 times more labour intensive than direct compression and coating of tablet cores. Compared with vitamins formulated as traditional dragees, sugar-coated and suspension-coated tablet cores exhibited superior stability over 12 months.CONCLUSIONS. The direct compression technology proposed for producing spherical tablet cores for subsequent coating instead of the traditional dragee technology will increase production efficiency, improve the stability of active components during storage, and reduce the duration and labour intensity of the production process. The proposed technology can be recommended to dragee manufacturers for implementation in industrial production.